Barotropic and baroclinic contributions to along-stream and across-stream transport in the Antarctic Circumpolar Current - Pena-Molino, B; Rintoul, SR; Mazloff, M (Journal of Geophysical Research: Oceans, 2014)
The Southern Ocean's ability to store and transport heat and tracers as well as to dissipate momentum and energy are intimately related to the vertical structure of the Antarctic Circumpolar Current (ACC). Here the partition between barotropic and baroclinic flow in the time-mean ACC is investigated in a Southern Ocean state estimate. The zonal geostrophic transport is predominantly baroclinic, with at most 25% of the transport at any longitude carried by the barotropic component. Following surface streamlines, changes in vertical shear and near-bottom velocity are large, and result in changes in the local partition of barotropic/baroclinic vertically integrated transport from 10/90% in the center of the basins, to 50/50% near complex topography. The velocity at depth is not aligned with the surface velocity. This nonequivalent barotropic flow supports significant cross-stream transports. Barotropic and baroclinic mass transport across the ACC is, on average, in opposite directions, with the net barotropic cross-stream transport being poleward and the net baroclinic equatorward. The sum partially cancels out, leaving a net geostrophic poleward transport across the different fronts between −5 and −20 Sv. Temperature is also transported across the fronts by the nonequivalent barotropic part of the ACC, with maximum values across the northern ACC fronts equivalent to −0.2 PW. The sign and magnitude of these transports are not sensitive to the choice of stream-coordinate. These cross-stream volume and temperature transports are variable in space, and dependent on the interactions between deep flow and bathymetry, thus difficult to infer from surface and hydrographic observations alone.